Perbandingan Hukum Pidana Konvensional dan Hukum Pidana Digital dalam Mengatur Kejahatan Berbasis Kecerdasan Buatan di Indonesia - Muhamad Reyhan Saputra Saputra; Muhammad Rofiq; Habib Dwi Putra; Rusma Renal Cholif; Asep Suherman (CV. ITTC INDONESIA, 2026)
The rapid development of Artificial Intelligence (AI) technology has serious implications for the legal order, particularly criminal law. Crimes involving AI systems whether as tools, subjects, or autonomous actors pose new challenges that cannot be adequately addressed by conventional criminal law. This study aims to analyze the comparison between conventional criminal law and digital criminal law in regulating AI-based crimes in Indonesia. The research method used is normative juridical with comparative and conceptual approaches. The results show that conventional criminal law has fundamental limitations in terms of legal subjects, causality, and criminal liability when dealing with AI systems. Digital criminal law as represented by the Electronic Information and Transactions Law (UU ITE) has also not comprehensively accommodated AI-based crimes. Indonesia needs special regulations (lex specialis) that place artificial intelligence as a separate object of regulation within the national criminal law system.